2013
DOI: 10.1002/ange.201305023
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Sulfonation of Enones with Sulfonyl Imines by Cooperative N‐Heterocyclic‐Carbene/Thiourea/Tertiary‐Amine Multicatalysis

Abstract: Scheme 1. Enantioselective catalytic sulfonation of enones. Tol = p-tolyl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(11 citation statements)
references
References 83 publications
0
10
0
1
Order By: Relevance
“…These results suggest that non-covalent interaction is likely to play an important role in controlling the enantioselectivity of our reactions. We thus examined non-covalent organic catalysts and found that using achiral thiourea3738394041 A1 as a co-catalyst could improve the e.r. values of 3a from 73:27 to 85:15 (entry 6 versus 4).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that non-covalent interaction is likely to play an important role in controlling the enantioselectivity of our reactions. We thus examined non-covalent organic catalysts and found that using achiral thiourea3738394041 A1 as a co-catalyst could improve the e.r. values of 3a from 73:27 to 85:15 (entry 6 versus 4).…”
Section: Resultsmentioning
confidence: 99%
“…The elegant strategy of NHC/bifunctional H‐bonding catalysis [54] was exhibited by Chi and coworkers, which was employed to perform an asymmetric sulfonation of sulfonylimines 93 with enones 94 (Scheme 30). [55] With the different combination of catalyst, the enone possessing aryl and alkyl group substituted at the β ‐position could be well compatible under the enantioselective conditions to afford product 95 or 96 . In this process, the NHC catalyst serves as an activator to cleave the N−S bond of sulfonylimine 93 , and leads to generation of a sulfinic anion nucleophile.…”
Section: Asymmetric Reactions Catalyzed By Multi‐organocatalystsmentioning
confidence: 99%
“…The Singapore Young Scientist Award, which is part of the President’s Science and Technology Awards, is administered by the Singapore National Academy of Sciences and supported by A*STAR (Agency of Science, Technology and Research), and is presented to researchers under the age of 35 years. Among the award winners were Qui Cheng Wei (National University of Singapore) and Yonggui Robin Chi (Nanyang Technical University; NTU), who has reported in Angewandte Chemie on N‐heterocyclic carbene organocatalysis,2a and on the use of multicatalysis in the enantioselective sulfonation of enones 2b. Chi studied at Hong Kong Baptist University and Tsinghua University, and carried out his PhD (awarded in 2007) under the supervision of Samuel H. Gellman at the University of Wisconsin–Madison.…”
Section: Awarded …︁mentioning
confidence: 99%